The ESG War: Public Pension Fiduciaries and Anti-ESG Laws - Alexander L. Norman (Washington University Journal of Law and Policy, 2024)
This Note analyzes the benefit of using environmental, social, and governance matters (“ESG”) by public pension plan fiduciaries when considering investment decisions, financial impacts, and calculation of risk. States have recently proposed or adopted anti-ESG legislation like boycott bills that limit the ability of state entities to do business with companies that boycott certain industries based on ESG concerns and anti-ESG regulations that restrict access of public pension fiduciaries to companies that utilize ESG criteria in their investment process. Anti-ESG state action raises important questions of whether public pension plan fiduciaries act within their duties to beneficiaries when making investment decisions based on ESG factors and whether state governments force public pension plan fiduciaries to violate their duties to plan beneficiaries by imposing anti-ESG investment restrictions on them. This Note argues that states should repeal anti-ESG laws because public pensioners will be harmed by decreased effectiveness on the part of fiduciaries and increased costs from litigation, investment losses, and industry divestment. As a solution, this Note proposes that states adopt permissive ESG policies like those stated in the 2022 Department of Labor Rule regarding private employer pensions governed under the Employee Retirement Security Income Act of 1974 (“ERISA”). Where states adopt ESG laws that parallel those of the private sector, public pension fiduciaries will be more able to comply with both state law and fiduciary duties in good faith while increasing investment returns.
Keywords: ESGInvesting; PublicPensions; FiduciaryDuties; AntiESGLaws; SustainableInvesting